Extraction By Physicochemical Methods Of Tara (Caesalpinia Spinosa) And Its Application In Sustainable Industry (Journal of Pharmaceutical Negative Results, 2023)
Tannins present in several plants are a valuable resource for various industries, being Tara one of the most important raw materials of these compounds, that is why the extraction process (at the laboratory level) of this plant was analyzed with the use of different solvents. First, samples of Tara powder (or flour) distributed by the Association of Farmers of Chimborazo were analyzed, and then the effect of the use of different organic solvents (ethanol, isopropanol, acetone and hexane) on the extraction yield with the Soxhlet technique in this powder was evaluated. In parallel, a hydroalcoholic extraction was performed under different operating conditions (ethanol content in the water-ethanol mixture equal to 50; 75 and 96% and different solid:liquid ratios equal to 1:5, 1:10 and 1:15) in search of optimizing the extraction process. It was determined that the best extraction conditions of Tara are produced with a hydroalcoholic extraction with a 75% ethanol content and a ratio equal to 1:10 solid:liquid at 40°C for 3 hours, reporting an average yield equal to 14.26% of the extract. The results obtained can provide the scientific basis for the design of industrial extraction processes and the subsequent use of Tara in the province of Chimborazo, providing benefits of various kinds to the producers of this plant in the region concerned.